FEBRE MACULOSA BRASILEIRA: CASUÍSTICA LABORATORIAL NOS ANOS DE 2004 A 2005 - Santos, FCP; Colombo, S; Nascimento, Elvira Maria Mendes do; Silva, Luiz Jacintho da (Revista do Instituto Adolfo Lutz, 2006)
Ver PDF.